2019
DOI: 10.1021/acsami.9b08429
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adhesion and Cohesion of Bioinspired Dry/Wet Pressure-Sensitive Adhesives

Abstract: The byssus-mediated adhesion of marine mussels is a widely mimicked system for robust adhesion in both dry and wet conditions. Mussel holdfasts are fabricated from proteins that contain a significant amount of the unique catecholic amino acid dihydroxyphenylalanine, which plays a key role in enhancing interfacial adhesion to organic and inorganic marine surfaces and contributes to cohesive strength of the holdfast. In this work, pressuresensitive adhesives (PSAs) were synthesized by copolymerization of dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 71 publications
5
103
0
Order By: Relevance
“…Molecular weight and T g values of polymers were measured using gel permeation chromatography (GPC) and differential scanning calorimetry (DSC) and are listed in Table (Supporting Information, Table S1, Figures S40, S41). Compared to the control PSA polymer (BA 91.4 % :AA 8.6 % ), the functional polymers had higher M w , which can be attributed to the enhanced non‐covalent and covalent interactions between the polymer chains owing to the presence of catechol groups, as described previously in more detail . The small variations observed between the molecular weight and T g of the functional polymers can further underline that physical properties of PSAs are not expected to be a major contributor to the differences noticed in their adhesive performance…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Molecular weight and T g values of polymers were measured using gel permeation chromatography (GPC) and differential scanning calorimetry (DSC) and are listed in Table (Supporting Information, Table S1, Figures S40, S41). Compared to the control PSA polymer (BA 91.4 % :AA 8.6 % ), the functional polymers had higher M w , which can be attributed to the enhanced non‐covalent and covalent interactions between the polymer chains owing to the presence of catechol groups, as described previously in more detail . The small variations observed between the molecular weight and T g of the functional polymers can further underline that physical properties of PSAs are not expected to be a major contributor to the differences noticed in their adhesive performance…”
Section: Resultssupporting
confidence: 58%
“…In a previous effort to improve their wet adhesion, we applied the mussel inspiration principles to the base PSA polymers and showed that catechol PSAs outperformed conventional benchmarks in different industry standard tests even at a low catechol content (ca. 3 mol %) . Apart from the inferior underwater performance, another major shortcoming of conventional PSAs is their poor cohesive strength and low toughness.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations